Caring for Carers? The Effect of Public Subsidies on the Wellbeing of Unpaid Carers - Joan Costa-i-Font; Francesco D'Amico; Cristina Vilaplana-Prieto (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the effect of long-term care (LTC) subsidies and supports on the wellbeing of unpaid caregivers. We draw on evidence from a policy intervention, that universalized previously means-tested caregiving supports in Scotland, known as free personal care (FPC). We document causal evidence of an increase in the well-being (happiness) of unpaid carers after the introduction of FPC. Our estimates suggest economically relevant improvements in the happiness (12pp increase in subjective wellbeing) among caregivers exposed to FPC and that provide at least 35 hours of care per week. Consistently, these results are larger among women and non-actively employed caregivers (17pp increase in happiness). Estimates are not driven by selection into caregiving (we find similar wellbeing effects among caregivers at baseline and caregivers throughout the sample), and are driven by income effects of FPC among caregivers.
Keywords: I18; J22; 330; caregiving; long-term care subsidies; subjective wellbeing; caregiver's wellbeing; Scotland